Pemeliharaan Drainase di Kota Pekanbaru - Adrian Pratama; Zaili Rusli (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
Drainage is an infrastructure system designed to channel water from one place to another. This study is based on Article 2 of the Regulation of the Minister of Public Works of the Republic of Indonesia No. 12 of 2014 concerning the Implementation of Urban Drainage Systems. This research aims to analyze the drainage maintenance carried out by the Public Works and Housing Office (PUPR) of Pekanbaru City using Dhillon B.S’s asset maintenance theory, which consists of two main indicators: preventive maintenance and corrective maintenance. This study employs a qualitative approach with data collection methods including in-depth interviews and field observations. The results indicate that drainage maintenance in Pekanbaru City faces several challenges, such as budget constraints, low public awareness, a shortage of skilled labor, outdated infrastructure conditions, and the impact of extreme weather conditions. The findings suggest that the drainage maintenance efforts by the PUPR Office of Pekanbaru City still encounter numerous challenges, particularly in technical aspects and community participation. Therefore, it is necessary to increase the budget and develop more competent human resources in the field of drainage maintenance. Additionally, more intensive public awareness campaigns on the importance of maintaining drainage cleanliness and the enforcement of penalties for violators should be strengthened. The utilization of modern technology, such as sensors and drone-based monitoring systems, can also serve as a solution to enhance the effectiveness of drainage maintenance. With these measures, it is expected that the drainage system in Pekanbaru City can function more optimally and sustainably.